The role of peripheral blood eosinophil counts in COVID‐19 patients. Issue 2 (13th July 2020) - Xie, Guogang; Ding, Fengming; Han, Lei; Yin, Dongning; Lu, Hongzhou; Zhang, Min
Abstract: Background: Coronavirus disease 2019 (COVID‐19) emerged in Wuhan city and rapidly spread globally outside China. We aimed to investigate the role of peripheral blood eosinophil (EOS) as a marker in the course of the virus infection to improve the efficiency of diagnosis and evaluation of COVID‐19 patients. Methods: 227 pneumonia patients who visited the fever clinics in Shanghai General Hospital and 97 hospitalized COVID‐19 patients admitted to Shanghai Public Health Clinical Center were involved in a retrospective research study. Clinical, laboratory, and radiologic data were collected. The trend of EOS level in COVID‐19 patients and comparison among patients with different severity were summarized. Results: The majority of COVID‐19 patients (71.7%) had a decrease in circulating EOS counts, which was significantly more frequent than other types of pneumonia patients. EOS counts had good value for COVID‐19 prediction, even higher when combined with neutrophil‐to‐lymphocyte ratio. Patients with low EOS counts at admission were more likely to have fever, fatigue, and shortness of breath, with more lesions in chest CT and radiographic aggravation, and longer length of hospital stay and course of disease than those with normal EOS counts. Circulating EOS level gradually increased over the time, and was synchronous with the improvement in chest CT (12 days vs 13 days, P  = .07), later than that of body temperature (12 days vs 10 days, P  = .014), but earlier than that of the negative conversion of nucleic acid assays (12 days vs 17 days, P  = .001). Conclusion: Peripheral blood EOS counts may be an effective and efficient indicator in diagnosis, Evaluation, and prognosis monitoring of COVID‐19 patients. Abstract : The circulating eosinophil counts decrease dramatically in most COVID‐19 patients. Low eosinophil counts and slow recovery may be related to severe conditions. The restore of eosinophil counts is synchronous with the improvement of chest CT, later than that of body temperature, but earlier than the negative conversion of nucleic acid assays. Abbreviations: COVID‐19, coronavirus disease 2019; CT, computed tomography; EOS, eosinophil.